Fatores de risco para síndrome metabólica em idosos assistidos em um hospital universitário em Belém/Pará. - MARTINS, Tainá Costa (2023)
OBJECTIVE: To assess the prevalence of risk factors associated with metabolic syndrome in elderly patients. METHODOLOGY: crosssectional study and descriptive analytica, quantitative, in which the population was constituted of 105 old aged pacients from both genders, with ages above 60 years or over, treated at an outpatient clinic of a University Hospital, from September to December 2019. The research was guided by a questionnaire composed of socioeconomic, anthropometric, clinical, biochemicals and lifestyle data. For the giagnosis of MS, the National Cholesterol Education Program Adult Treatment Panel III (NCEPATP III) criteria were used. RESULT: Most participants were female (72.4%). The prevalence of metabolic syndrome (MS) was 75.2%, of the isolated components of MS, 65.7% were hypertensive, 63.8 % had hyperglycemia, 60% had decreased HDLc and 75.2 % had abdominal obesity. As for the risk factors for MS, the mean body mass index (BMI) remained above 28.0 kg/m2 for both sexes, most of the elderly were ex alcoholics or did not consume alcohol (87.6% ) and former smokers or nonsmokers (93.3%), however, sedentary lifestyle was significantly high (73.3%). There were no significant differences in the frequency of consumption of healthy and unhealthy dietary markers between the elderly with and without MS. CONCLUSION: MS and its individual components (hypertension, hyperglycemia, reduced HDLc and abdominal obesity) have a high prevalence in the elderly population studied. Among the risk factors related to lifestyle, there was a significant prevalence only of sedentary lifestyle. Therefore, further studies are needed to analyze the longterm relationship of the risk factors mentioned in this study with MS.